Responding to Domestic Minors Sex Trafficking (DMST): Developing Principle-Based Practices. Issue 4 (1st October 2016) - Wachter, Karin; Cook Heffron, Laurie; Busch-Armendariz, Noël Bridget; Nsonwu, Maura B.; Kammer-Kerwick, Matt; Kellison, Bruce; Jones, Amy L. E.; Sanders, Gretchen M.
ABSTRACT: Over the last decade, modern slavery has emerged as a major social-justice issue. Many new organizations in the United States have begun serving survivors of domestic minor sex trafficking (DMST), while others have expanded their services to include this vulnerable population in their mission. This qualitative study describes the principle-based practices that emerged from structured interviews with staff employed at five well-established organizations in the United States whose missions include providing direct services to DMST survivors. Thematic analysis identified five guiding principle-based practices for working with DMST survivors: nurture the humanity and dignity of clients; contextualize the needs of survivors within a broader social-justice framework; prioritize the immediate and practical needs of clients; support of the dynamic nature of survivors' healing; help identify and engage community and professional partners who are essential to the work of serving DMST survivors and ending sex trafficking. This research enhances the field's understanding of principle-based practice with DMST survivors and encourages those working with DMST survivors to critically consider the principles behind their practice. The findings are particularly important given complex vulnerabilities and needs, and the significant rise in the number of untrained organizations providing services to survivors.